Utilization of Yard for Vegetable Hydroponics in Serut Village, Panti Sub-District, Jember District - parawita dewanti (Asian Journal of Innovation and Entrepreneurship, 2018)
Vegetables as a horticultural product is a food source that is always consumed by humans daily, including in urban areas. Assorted Vegetables can be eaten raw or processed and it takes as a decoration on the food. Needs vegetables including lettuce, green pakcoy and other vegetables from day to day continues to increase. Therefore, it needs supply of vegetables from the area around the town of Jember including Serut Village, District Panti Sub-District, Jember District. Serut village has the potential of non-agricultural land could be developed into a producer of vegetables. Empowerment yard area for the cultivation of vegetables will be achieved if supported by an efficient hydroponic cultivation techniques and the empowerment of human resources are adequate. Empowerment of rural communities is expected to increase the quantity and quality of vegetable production of lettuce, cabbage, and other vegetables as well as to support sustainable vegetable production. Through this hydroponic cultivation of fresh vegetables will be produced continuously, scheduled and able to add value to the revenue for the community.